Hemicalcaneal reconstruction with a 3D printed custom-made prosthesis after partial calcanectomy due to a malignant bone tumor - D'Arienzo, Antonio; Ipponi, Edoardo; Ferrari, Elisa; Campo, Francesco Rosario; Capanna, Rodolfo; Andreani, Lorenzo (Acta Biomedica Atenei Parmensis, 2023)
The malignant bone tumors of the calcaneus are extremely uncommon lesions. Surgical approach can consist in either an amputation or in a limb sparing procedure, depending on the width and the location of the neoplasm. Although several reconstructive options have been proposed to fulfill the bone defect in those cases that received a selective resection, to this date a consensus reconstructive approach is far from being established. Among the alternatives described in literature, 3D printed custom-made prostheses represent one of the most intriguing and promising reconstructive options. Herein, we report our experience of a spindle cell bone sarcoma of the calcaneus treated with selective resection of the anterior segment of the calcaneus and further reconstruction with a 3D printed custom-made prosthesis, based on patients’ own anatomy. The posterior calcaneus and the insertion of the Achilles tendon were preserved. The resection was performed with wide margins and no major complication occurred through the intra-operative or post-operative intercourse. At her latest follow-up, our patient showed good functional results and was continuously disease free. Our outcomes therefore suggest that a partial prosthetic replacement of the anterior calcaneus with preservation of the Achilles insertion site may represent a safe and effective solution for cases that required the resection of the anterior calcaneus due to a malignant bone tumor